BENTUK PERMINTAAN SOPAN DALAM BAHASA INGGRIS DAN BAHASA TONSAWANG (SUATU ANALISIS KONTRASTIF) - MATU, TANIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTS This studyÂ  entitled â€œ Bentuk Permintaan Sopan dalam Bahasa Inggris dan Bahasa Tonsawang: Suatu Analisis Kontrastifâ€ is aimed to be presented as a requirement for Sarjana Degreeâ€Ÿ at Faculty of Humanities Sam Ratulangi University. The research question to be answered are what are the forms of polite request in english and Tonsawang language and are there any similarities and differences in both these two language. In terms of methodology, the writer uses the theory of Lado and Leech. This research has been done through field research and using descriptive method and contrastive analysis by Lado. Data of Tonsawang language are found by interviewing the native speakers of Tonsawang language who lived in Tombatu district. English data have been taken from some English book. The result of this reseacrh shows that English and Tonsawang Language have similarities, that EnglishÂ  and Tonsawang language have sentence patterns which are used to request the hearer to do something according to what the speaker wants. The differences of both these two languages lie in their forms. Key Words: The form of polite request, English and Tonsawang Language, Contrastive